Presentation: Ruggiero Romano, the Traveler - Flores Galindo, Alberto (1983)
The sixty years of Ruggiero Romano are an exceptional occasion to refer to the work of a prolific and multiple historian, linked to Peru in many ways. Initially, this link can refer to certain bibliographic dates. Romano has been carrying out long-term research on coca for several years, those "poor leaves" through which the economic and cultural history of the country can be reread.